Review of some mites (Acari: Laelapidae) associated with ants and bumblebees in Western Siberia, Russia - Joharchi, Omid; Tolstikov, Andrei V.; Khaustov, Alexander A.; Khaustov, Vladimir A.; Sarcheshmeh, Mohammadhassan Abbasi (Zootaxa, 2019)
This paper reports on ten species of laelapid mites associated with ants and bumblebees in Western Siberia. Androlaelaps myrmecophilus (Evans & Till), Cosmolaelaps dendrophilus (Davydova), C. neocuneifer (Evans & Till), C. siberiensis Joharchi sp. nov., Gaeolaelaps praesternalis (Willmann), Holostaspis isotricha Kolenati, H. montana (Berlese) and H. oophilus (Wasmann) were collected from ants’ nests, and Pneumolaelaps hyatti (Evans & Till), P. marginepilosa (Sellnick) on bumblebees. The new species is described and illustrated based on morphological characters of the adult female.